Гроза над Цхинвалом: роман / В. И. Пищенко, А. В. Марков - Пищенко Виталий Иванович (Военные приключения, 2009)
Экземпляры: ф.15 (20150305) / Инвентарный номер: 56327 / Цена: 100.00 / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: П 36 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44